Two isomeric and distinguishable H2S fluorescence probes for monitoring spoilage of eggs and visualizing exogenous and endogenous H2S in living cells. Issue 1 (19th November 2019) - He, Yuqian; Zhao, Bing; Kan, Wei; Ding, Limin; Yu, Zhaochuan; Wang, Mingyue; Song, Bo; Wang, Liyan
Abstract : Accurate fabrication of fluorescence probes to efficiently monitor and detect H2 S levels in the fields of foodstuffs and physiology is crucial. Abstract : Accurate fabrication of fluorescence probes to efficiently monitor and detect H2 S levels in the fields of foodstuffs and physiology is crucial. Herein, we report two isomeric phenanthro[9, 10- d ]imidazole benzene sulfonamide-derived fluorescence probes (PI-2-SA and PI-4-SA ), both of which display remarkable responses toward H2 S over other analytes. The spectral characteristics of the two probes were investigated and are discussed in detail. By comparison, PI-2-SA was specific, sensitive (the limit of detection was ca. 12.3 nM), rapid (within ≤3 min) and dynamic (the rate constant was 0.02 s −1 ). Significantly, PI-2-SA was proved to be effective in monitoring the shelf-time progress of egg samples in real time as well as in the imaging of exogenous and endogenous H2 S in HeLa cells.